The Performance of Foodpanda During The Pandemic: A Study of Consumers' Perspective - Azimah Shazeeda Suleiman; Daisy Mui Hung Kee; Asraaf Mohmed Azmi; Da Wei Chan; Jhing Hoong Aw; Wulan Ruhiyyih Khanum; A.A. Gde Satia Utama (AIBPM Publisher, 2021)
Foodpanda is a food delivery service widely known among Malaysians for ordering food and groceries. Due to the pandemic outbreak, the usage of Foodpanda apps has rapidly increased. The objective of the study is to identify the performance of Foodpanda during the pandemic and if Foodpanda is the favorite food delivery service. A total of 150 Foodpanda customers participated in the survey. Results indicated that Foodpanda is ranked as the most favorite food delivery service in Malaysia. The results also indicated that customer satisfaction and loyalty are the key elements of the better performance of Foodpanda. The recommendation is presented.